(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Over the years, the world has become common to pandemic diseases in humans with lot of ailments and untreated infectious disorders. Most of the laboratories across the globe run in with under developed vaccines and drugs for many diseases for its procurement and prevention. But the bioavailability of the drug in the market is less reached due to high cost and etc. In the current situation, plant saps and its extracts are used to counteract with the pathogens based on the information in traditional medicine. Most of the phytochemical enriched herb, weed or plants available commonly are used for treatments of various diseases. One of the herbs found is Mollugo verticillata (commonly known as ‘green carpet weed’). It is commonly used in treating fever, aches and other various ailments and it shows promising activity in pharmacological properties due to the presence of phytoconstituents like terpenoids, saponins and flavonoids. Finally, the plant extract has enormous medicinal importance. This review is a collection of overall research work on Mollugo verticillata plant and their medicinal compounds present.